Kelayakan dan Strategi Pengembangan Usaha Pembudidayaan Tanaman Hias di Kompleks Perumahan Bekasi (Kasus Usaha Tanaman Hias Adenium pada Lahan Terbatas) - - Adelita; Musa Hubeis; Darwin Kadarisman (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2010)
Decorative Plant business is relative newly and in this time is to be developed. Development of decorative plant business in the future having bright enough prospect, because enthusiasm to this plant more increasing. Business decorative plant have opportunity to be developed and improved with intensification and extensification, now days start to be developed by rent of decorative plant in the hotels. From the other of decorative plant which exist in Indonesia, Adenium is most like decorative plant. Adenium is very popular among hobbies. This matter is caused uniqly and bright color. Activity of Adenium is have a problems, which is technical problem of conducting and marketing That problem causing productivity become to lower in produce Adenium and quality, but for farmer in the Bekasi problem is added by limited place cause land is so expensive price. According to the matter has been done by Feasibility and Strategy Development of plant in Real Estate of Bekasi, with : (1) analyze  the feasibility of decorative plant of Adenium, (2) compiling strategy development  in improving sale of decorative plant Adenium. This study is has been doing in real estate of Bekasi, with four responder merchant of decorative plant Adenium. Using method study is descriptive analysis, analysis Feasibility study (BEP, B/C Ratio and of Payback Period) and Strengths, Weakness, Opportunities and Threats (SWOT) analysis. From financial analysis result indicate that the business decorative plant of Adenium if feasible to be implemented in limited pace because can give advantage in payback period 7.47-22 months and get value of Rp. 3.121.665 - Rp. 3.813.750. While strategy able to be done by using marketing strategy by marketing mix, that is strategy product, price, promotion and place.